Effect of fluid and electromagnetic braking force on the falling motion of a permanent neodymium magnet - Urquiaga Vásquez , Ausberto Wilson (2025)
In the present work, the effect of the fluid and the electromagnetic braking force on the falling motion of a permanent neodymium magnet was determined. The magnet was introduced through the metal bar slightly submerged into the fluid and the magnet was released for movement through the metal bar. The vertical movement of the magnet was filmed with a Samsung S8 video camera that has a rate of 240 frames per second. The video was analyzed with the Tracker software to calculate the parameters and obtain the kinematic equations of the model. Finally, from the results obtained, it was concluded that the viscosity force and the electromagnetic braking force help to dampen the falling movement of the neodymium magnet through the metal bars. Likewise, it was determined that the electromagnetic braking force on the magnet is greater than the viscosity force.